Ritual as a method of social memory content transfer; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Utkina A. N. Anna Nikolaevna; Mironova V. E. Veronika Evgenievna; Loyko O. T. Olga Timofeevna; Volkov A. E. Alexandr (2016, 2016)
Title screen